What affects the timing of tropical cyclone formation within a monsoon trough? - Zong, Huijun; Wu, Liguang (Frontiers in Earth Science, 2023)
Although favorable environmental conditions for tropical cyclone (TC) formation have been known for a long time, physical factors that influence the timing of TC formation remain unclear. Idealized numerical simulations are conducted by placing identical tropical disturbances (TDs) in various locations within the monsoon trough to examine what affects the timing of TC formation. The timing of TC formation is evaluated by the development time of TDs, which ranges from 60 hours to 189 hours. Vertical misalignment, defined as the vortex tilt between mid-and low-level circulation centers of the TD, is closely related to TC formation timing. The mid-and low-level circulation centers tend to be vertically aligned when TC formation time approaches. Different from previous studies, vertical misalignment does not entirely depend on vertical wind shear. Vertical misalignment is directly induced by inconsistent translation speeds between the mid-and low-level circulation centers. However, the steering flows for the mid-and low-level circulation centers cannot fully explain the differences in translation speeds. Additionally, there is no strong connection between environmental conditions and TC formation timing for the TDs within the monsoon trough. Rossby energy dispersions of TDs and terrain effects have some impacts on TC formation timing but are not decisive in this study.